Discussing Javanese House Using Vitruvius Theory - Mean Pisei; Ikaputra Ikaputra (Universitas Muhammadiyah Surakarta, 2020)
Javanese House is well-known as one of the significant vernacular architecture Indonesia which is built by indigenous people. The local builder holds on the philosophical and cosmological concept for the spatial plan arrangement of the Javanese house. Each space has its proper function and meaning which is reflected from the society and culture of Java. Javanese architecture has been used on the human scale as its proportion design that gives both aesthetic and symbolic dimension. In addition to the aesthetic and functional value of Javanese house, the indigenous builder builds their house by using their traditional construction method, which is known as teknologi tepat guna. This construction method is not only appropriate to their local availability of material and environment but also have high strength and durability. The vernacular architecture of Java is the product of indigenous people from many times of trials and errors. The aim of this study is to discuss how do indigenous people of Java interpret the Vitruvius theory into their Javanese house. This final design might show that the local builder has followed the application of Vitruvius theory: Firmitas (strength), Utilitas (functionality), and Venustas (beauty).